An THE IMPLEMENTATION OF SSCS (SEARCH-SOLVE-CREATE-SHARE) MODEL WITH WORKSHEET TO BUILD STUDENTS’ CREATIVITY ON MAKING SIMPLE WATER PURIFIER IN CHEMISTRY CLASSROOM - Wahyu, Wawan; Suryatna, Asep; Amalia, Gita (Unnes Science Education Journal, 2019)
The aim of this research is to describe the implementation of SSCS (search-solve-create-share) model with worksheet to build students’ creativity on making simple water purifier in chemistry classroom. The implementation of this model including activities of chemistry teacher and the students of VIIth grade junior high school in Bandung. The research method is used in this study is design research according to Plomp. The subjects of this are 1 chemistry teacher and 24 students to implementation and 3 observers. The instruments of this research are activity observation sheet of teachers and learners. Data processing result of this research use scoring process based on Likert scale then interpretation of percentage according to Riduwan. The results of this research describing that activity of teacher and the students showed very good.